Pediatric orthopedics for primary care physicians - Weiner, Dennis S. (Cambridge University Press, 2004)
This revised and extended new edition retains the features that made the first edition such a popular text for pediatricians and primary care physicians: orthopaedic disorders are arranged according to age of onset and also according to their frequency of occurrence, and this is supplemented with helpful guidelines for orthopaedic referral. Distilling a vast wealth of the author's experience in this area, the book provides a user-friendly, concise and readable account of all the main pediatric orthopaedic complications, with the addition in this new edition of helpful 'pearl' boxes to highlight salient features of the given disorder. A new chapter on the genetics of these disorders provides additional useful background. The new edition is also richly illustrated throughout with many new radiographs and line drawings to supplement the text. Written specifically for residents in pediatrics and family practice, this volume will help doctors provide the optimal care of these patients.